2017
DOI: 10.1371/journal.pone.0181205
|View full text |Cite
|
Sign up to set email alerts
|

Is directly observed tuberculosis treatment strategy patient-centered? A mixed method study in Addis Ababa, Ethiopia

Abstract: IntroductionThe directly observed treatment, short course (DOTS) strategy has been considered as an efficacious approach for better tuberculosis (TB) treatment adherence and outcome. However, its level of patient centerdness has not been studied and documented well. Hence, the study aimed to determine the level of patient centeredness’ of the DOTS.MethodThe study used explanatory sequential mixed method design in Addis Ababa, Ethiopia. The study employed an interviewer-administered questionnaire with 601 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Alternative strategies need to be explored in the Ethiopian settings where the frequency of G6PDd is very low and varies substantially between sites; blanket deployment of diagnostic tests might not be cost-effective. Strategies such as directly observed treatment (DOT), close medical supervision for potential PQ-induced haemolysis, as in tuberculosis care [ 63 ], using its extensive health extension workers program (with counseling on how to recognize symptoms and signs of haemolytic anaemia) or approaches tailored to local context considering the varying geographic distribution of the deficiency could be plausible options.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative strategies need to be explored in the Ethiopian settings where the frequency of G6PDd is very low and varies substantially between sites; blanket deployment of diagnostic tests might not be cost-effective. Strategies such as directly observed treatment (DOT), close medical supervision for potential PQ-induced haemolysis, as in tuberculosis care [ 63 ], using its extensive health extension workers program (with counseling on how to recognize symptoms and signs of haemolytic anaemia) or approaches tailored to local context considering the varying geographic distribution of the deficiency could be plausible options.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous local study, while supportive relation with health professionals contributed positively, lack of adequate communication was among barriers to treatment adherence [ 26 , 27 ]. Another study in Addis Ababa also showed that DOTS was provided with limited patient-centered TB care [ 28 ]. Similarly, confirming patients’ relationship with treatment providers appeared to influence adherence, researches carried out in other parts of the world revealed that poor follow-up by providers in Indonesia and India [ 29 , 30 ] and maltreatment by providers in India, Pakistan and Burkina Faso [ 17 , 21 , 31 ] resulted in non-adherence, whereas other studies set in Vietnam, Pakistan and Mexico noted the positive impact of increased provider-patient contact on adherence [ 10 , 25 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medecins Sans Frontieres (MSF) developed and implemented a home-based MDR-TB treatment programme in Northern Uganda, which was found to be acceptable to patients, families, communities and healthcare workers [122]. An Ethiopian study investigated the extent to which the directly observed treatment short course (DOTS) strategy is patient-centred, showing that it falls short of achieving such care [123].…”
Section: The Paucity Of Person-centred Carementioning
confidence: 99%